Chitosan/bioactive glass nanoparticles composites for biomedical applications - Luz, Gisela (2012)
Nanocomposite films based on a chitosan blend with bioactive glass nanoparticles (BG-NPs) with different formulations, namely SiO2:CaO:P2O5(mol.%) = 55:40:5 and SiO2:CaO:P2O5:MgO(mol.%) = 64:26:5:5 were produced in order to develop systems with applicability in guided tissue regeneration. The zeta (ζ )-potential of the BG-NPs containing magnesium was found to be lower than the other formulation and the corresponding composite with chitosan was the most hydrophilic. The bioactive character of the biomaterials was also assessed in vitro by immersion of the materials in simulated body fluid, followed by scanning electron microscopy (SEM) and energy-dispersive x-ray spectroscopy evaluations. SaOs-2 osteoblastic-like cells were seeded on the different nanocomposites and their behavior was followed by SEM observations, cytotoxicity assessments, DNA quantification and alkaline phosphatase analysis. The introduction of the inorganic component in the chitosan matrix had a positive effect on the biological response of the membranes. The developed nanocomposite films are potential candidates for regenerating damaged bone tissue and could be useful in orthopedic and maxillo-facial applications.